ANALISIS CEMARAN LOGAM TIMBAL (PB) DAN TEMBAGA (CU) DALAM TEPUNG TERIGU DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - MARIA CARITAS N.A.I LOGA; NORMA TIKU KAMBUNO (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
National Standardization Agency of Indonesia in the SNI No. 01-3751-2006 on wheat flour as food ingredients include Lead (Pb) and Copper (Cu) as metal contaminants. Consumption of food or beverages that contain heavy metal contamination on - constantly, will lead the process of bioaccumulation of metals. The impactsare a disorder of the nervous system, stunted growth, reproductive disorders, paralysis and premature death, and may also reduce the level of intelligence of children. The purpose of this study was to determine the metal content of Lead (Pb) and Copper (Cu) in wheat flour brand Gatotkaca and compare with SNI requirements. This study uses a dry destruction by Atomic Absorption Spectrophotometry. The analysis showed that wheat flour brand Gatotkaca in the Oeba market Kupang containing lead (Pb) metallic of 2.2983 mg/kg while the metal content of copper (Cu) of 2.7813 mg / kg. It was concluded that the metal contamination levels of lead (Pb) are not match while the metal concentrations of copper (Cu) are match with SNI.